Molecular analysis of SSN6, a gene functionally related to the SNF1 protein kinase of Saccharomyces cerevisiae. - Schultz, J (1987)
Mutations in the SSN6 gene suppress the invertase derepression defect caused by a lesion in the SNF1 protein kinase gene. We cloned the SSN6 gene of Saccharomyces cerevisiae and identified its 3.3-kilobase poly(A)-containing RNA. Disruption of the gene caused phenotypes similar to, but more severe than, those caused by missense mutations: high-level constitutivity for invertase, clumpiness, temperature-sensitive growth, alpha-specific mating defects, and failure to homozygous diploids to sporulate. In contrast, the presence of multiple copies of SSN6 interfered with derepression of invertase. An ssn6 mutation was also shown to cause glucose-insensitive expression of a GAL10-lacZ fusion and maltase. The mating defects of MAT alpha ssn6 strains were associated with production of two a-specific products, a-factor and barrier, and reduced levels of alpha-factor; no deficiency of MAT alpha 2 RNA was detected. We showed that ssn6 partially restored invertase expression in a cyr1-2 mutant, although ssn6 was clearly not epistatic to cyr1-2. We also determined the nucleotide sequence of SSN6, which is predicted to encode a 107-kilodalton protein with stretches of polyglutamine and poly(glutamine-alanine). Possible functions of the SSN6 product are discussed.